Influence of Viral Contents on the Rapid Spread of Information on the Social Media Platforms in Nigeria - G.O. Igben, Harvey; Endurance Acchugbue, Okiemute (British Journal of Marketing Studies, 2024)
This paper highlighted the influence of viral content on the rapid spread of information on the social media platforms. This paper raised four (4) research questions as guide. The descriptive survey design was used in this investigation. The study population was three hundred and fifty (350) social media users. The sample size of one hundred and thirty (130) social media content creator and users was adopted relying on the simple random sampling technique. The questionnaire was used as the instrument for collecting data. Descriptive statistics specifically tables and mean were used for the analysis of data collected. Findings shows that emotional connection, visual appeal, relevance, social proof, convenience, controversy, novelty, humour, timeliness and interactive elements are the factors that contribute to the rapid spread of viral content on social media platforms. The paper concluded that the potential consequences of the rapid spread of viral content to individuals and society include dissemination of false information which causes harm to individuals and society, feelings of anxiety and stress, increased social media addiction, negative impact on mental health for some individuals, anxious feelings, and stress due to the constant stream of alarming information. This paper recommended that platforms should establish, enforce clear, stringent content moderation policies that address the unique challenges posed by viral content and development of advanced algorithms that should be regularly updated to adapt to evolving tactics used by those spreading false information, which should work in tandem with human review processes to ensure a balanced approach.